Food Reputation Map (FRM): Italian long and short versions' psychometric features. (July 2017) - Bonaiuto, Marino; De Dominicis, Stefano; Fornara, Ferdinando; Ganucci Cancellieri, Uberta; Petruccelli, Irene; Bonaiuto, Flavia
Highlights: Food is defined as social agent: its features and effects on contexts and individuals. Food Reputation Map (FRM) measures 23 specific indicators for a target food's reputation. Each FRM short version's specific indicator is measured via four best markers. The overall FRM score converges with other global measures of food reputation. FRM could inform decisions within applied contexts relating to health, marketing, etc. Abstract: Reputation is a social-psychological variable influencing behavioural choices in general. Drawing from current literature on persons and organizations, the concept of reputation is applied to food conceived as a social agent: Food reputation pertains to all the beliefs about a food object, its antecedents (i.e., its production effects) and its consequences (i.e., its consumption effects). Food Reputation Map (FRM) is a theoretical framework and a methodological tool encompassing six main areas (synthetic indicators) of food reputation, further articulated into 23 markers (specific indicators): they gauge people evaluative perception of a food's intrinsic characteristics, its effects on the context (e.g., during its production phase), and its effects on the individual (e.g., during its consumption phase). Two studies were conducted at the Italian national level on over three thousands participants ( N1 = 2693; N2 = 585–out of 1308 total participants). Multivariate statistical analyses are used to build FRM as a psychometric tool for measuring food reputation. In each of the two studies (first long, and then short FRM version), results of exploratory factor analysis and Cronbach's alpha allow to select the best items for each synthetic and specific indicator, on the basis of its factorial structure and internal consistency. Both theoretical and practical implications are discussed.